Тhe peculiarities of epidemiological and socio-economic importance of respiratory diseases in the modern period - A. A. Kuzin; V. N. Emel'yanov; A. P. Gubanov (Эпидемиология и вакцинопрофилактика)
Relevance. In recent years, the world has seen a high prevalence and mortality from respiratory diseases. This entails high economic costs for most developed countries. Objective: to conduct a content analysis of sources that provide information on the incidence and the population and soldiers of respiratory diseases and indicators characterizing it.Materials and methods. A content analysis of 50 sources of scientific literature devoted to the problem of respiratory diseases and published in 2009–2017 was conducted using domestic and foreign databases (PubMed, eLibrary, KiberLeninka). The paper also considered information from the Federal State Statistics Service of the Russian Federation (Rosstat). The incidence rates of this type of pathology among the population over a long period (2000–2016) and among military personnel for 2003–2016 were analyzed.Conclusion. Based on the analysis of the data, risk factors for the development of respiratory diseases were identified, as well as socio-economic damage caused to the militarians with community-acquired pneumonia.